Analisis Kesalahan Penggunaan Fukushi Kanarazu, Kitto, Zettai(ni) dan Zehi pada Mahasiswa Prodi Pendidikan Bahasa Jepang UNNES - Nursanti, Anisa Indah; Supriatnaningsih, Rina (Universitas Negeri Semarang, 2019)
The purpose of this study was to find out the errors and any factors that caused errors in the use of kanarazu, kitto, zettai (ni) and zehi on students of the UNNES Japanese Language Education Study Program. The population in this study were students of the 2015 Japanese Language Education Study Program UNNES. The sample was taken by a random sampling technique, which was 37 students. Retrieval of data using the test method as many as 20 questions. The results showed an average percentage of fukushi use errors of 71% in the high category. The highest error rate for using fukushi is zehi. The cause of the error is due to a lack of understanding of fukushi use, the similarity of meaning between the four fukushi, less careful attention to the patterns that follow, so they do not understand the context of the four uses of fukushi.